1994
DOI: 10.1159/000239194
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging in Children Receiving Quinolones: No Evidence of Quinolone-lnduced Arthropathy

Abstract: Twenty-nine children with cystic fibrosis (CF) were investigated for quinolone-induced arthropathy. Magnetic resonance imaging (MRI) was performed in 14/14 children treated with ofloxacin or ciprofloxacin and in 10/15 of those never treated with quinolones. The frequency of pathologic MRI findings, concerning cartilage thickness, careful analysis of the cartilage structure, presence of edema, cartilage-bone borderline and the presence of fluid in joints did not show any difference between both groups. Thus the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…The pediatric usages of fluoroquinolones have been restricted because there were some concerns such as risk of arthropathy for the use of quinolones in children. However, the recent reports say the safety profile of fluoroquinolones in children is not substantially different from that of adults, and these types of drugs in the treatment of otolaryngology infections in children were effective [32][33][34]. It might be possible that any extension of the indications of off-label use of fluoroquinolones in pediatric patients would be given after large clinical trials in children, although Sazawal et al [35] concluded in their report that quinolone should be continued as the second-line drugs to treat children, only after failure of an early treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The pediatric usages of fluoroquinolones have been restricted because there were some concerns such as risk of arthropathy for the use of quinolones in children. However, the recent reports say the safety profile of fluoroquinolones in children is not substantially different from that of adults, and these types of drugs in the treatment of otolaryngology infections in children were effective [32][33][34]. It might be possible that any extension of the indications of off-label use of fluoroquinolones in pediatric patients would be given after large clinical trials in children, although Sazawal et al [35] concluded in their report that quinolone should be continued as the second-line drugs to treat children, only after failure of an early treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Since an arthropathic toxicity has been observed in growing animals, the quinolone antibiotics are generally not recommended for systemic use in children [22]. However, clinical, radiological and histopathological examinations of patients receiving oral ciprofloxacin have shown no evidence of arthropathy [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed 10 studies that, radiographically or pathologically by autopsy, evaluated pediatric and adolescent patients aged 5 days-24 years who were treated with ciprofloxacin or ofloxacin for 7 days-10 months [22][23][24][25][26][27][28][29][30][31]. These studies found no evidence of the cartilaginous pathology described in the original fluoroquinolone animal studies (table 1) [12][13][14][15][16][17][18][19].…”
Section: Studies With Histopathologic or Radiological End Pointsmentioning
confidence: 99%
“…Of the 9 radiographic studies that evaluated large joints, 5 used X-ray and 5 used MRI [22][23][24][25][26][27][28][29][30]. None reported pathologic changes detected as a direct effect of therapy.…”
Section: Studies With Histopathologic or Radiological End Pointsmentioning
confidence: 99%
See 1 more Smart Citation